New perspectives on communicating in business with technology - Cram, Carol M. (Boston : Thomson Course Technology, 2007)
This work provides an overview of business writing and its uses of technology as tools for communication, including electronic communication, routine correspondence, persuasive correspondence, longer communications, promotional materials development, oral communications, persuasive presentation development, and creating/distributing job search documents.
On cover: "Features Microsoft Word, PowerPoint and Outlook 2003."
Includes glossary and index.
Instructional CD-ROM available which includes data files, instructor's manual and other resources.
Grades 9 and up.
Keywords: Business communication -- Technological innovations; Business writing -- Technological innovations; Business presentations -- Technological innovations